Induction machines diagnosis by the time's harmonics - Abderrrahim Allal; Abderrahmane Khechekhouche; Zied Driss (International Journal of Energetica)
The induction motor is currently becoming the key element of most industrial equipment. Despite these advantages, a certain number of constraints of very different natures can affect the lifetime of this machine, causing considerable economic losses. This work is the study experimental of defects for an asynchronous machine  (with and without defect). After having described the main defects that can occur on these. In this study,  we propose a method called induction machines diagnosis by the time's harmonics. This technique is based to study the influence of a defect of short-circuiting on the studied induction motor, we will find the rank of the harmonic of the most influenced by the number of the rank default. this study will find the diagnostic index of induction motor with stator default using the time harmonics. The results obtained show that the 3rd order time-harmonic is very sensitive compared to the other harmonics.